MATHEMATICAL CONCEPTS IN PRIMARY EDUCATION (International journal of artificial intelligence, 2026)
This scientific article highlights the theoretical and practical foundations of developing mathematical concepts in primary school students. The article analyzes the stages of mathematical thinking development, the age and psychological characteristics of students, methodological approaches to forming mathematical concepts, and the importance of modern pedagogical technologies. The effectiveness of using game technologies, interactive methods, problem-based situations, and practical exercises in developing concepts related to numbers, shapes, quantity, time, space, and logical thinking in primary education is demonstrated. Furthermore, the article extensively discusses the enhancement of students’ independent thinking, analytical abilities, creative approaches, and mathematical literacy in everyday life through the development of mathematical concepts. During the research, it was substantiated that the use of innovative methods in primary mathematics lessons contributes to students’ conscious acquisition of knowledge, solid mastery of mathematical concepts, and increased interest in academic subjects.